2012
DOI: 10.1155/2012/517059
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Systemic Lupus Erythematosus and Thyrotoxicosis: The Diagnostic Value of Antihistone Antibodies

Abstract: We report four female patients with Graves' disease with positive ANA antibodies and possibility for development of systemic lupus erythematosus. All four patients have been treated with antithyroid drugs. SLE symptoms have appeared from 4 to 12 months after the beginning of therapy with methysol in two of them. The third patient had no symptoms for SLE, but her ANA, anti-DNA, and antihistone antibodies had been positive at the time of the onset of thyrotoxicosis. The fourth patient had alopecia areata with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This same observation was made by Mokhtar [8]. In other cases lupus can occur after the diagnosis of Basedow disease as Toujani observed [7] and Baleva [9]. It is also possible that these two conditions are concomitant as observed by Baili.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This same observation was made by Mokhtar [8]. In other cases lupus can occur after the diagnosis of Basedow disease as Toujani observed [7] and Baleva [9]. It is also possible that these two conditions are concomitant as observed by Baili.…”
Section: Discussionsupporting
confidence: 71%
“…For the first case, it was systemic lupus associated with Graves 'disease and for the second Graves' disease associated with anti-phospholipids syndrome. Baili [3] has also described the association as well as Baleva [9], in 4 cases of systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 94%
“…The studies reported on the order of appearance of AITD and systemic autoimmune diseases are debatable [9, 22, 23]. The order of appearance of AITD and systemic autoimmune diseases had been reported in one study, but with a very low population size ( n = 4) [24]. We have reported here the most comprehensive analysis with 14825 subjects to show the order of emergence of the systemic autoimmunity in AITD subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Systemic lupus erythematosus (SLE) is another autoimmune disease in which autoantibodies against a panoply of self‐antigens can affect multiple systems, including the skin, joints, and kidneys 2 . Some case reports have linked Graves' disease to incident SLE 3,4 . It has also been reported that antithyroid drugs used to treat Graves' disease can induce SLE 5 .…”
Section: Introductionmentioning
confidence: 99%